Analisis Pengaruh Unsur-Unsur Tempatan Dalam Kitab Al-Sirat Al-Mustaqim Karya Shaykh Nur Al-Din Al-Raniri - Jamalludin, Hashim (2013)
This paper is a study of the influence of local jurisprudence elements found in the writing of the manuscript Al-Sirat al-Mustaqim ( Kitab al-Taharah and al-Salah) works of Shaykh Nur al-Din al-Raniri (d. 1068H). Al-Sirat al-Mustaqim is the first book of fiqh written in Malay language in the archipelago.A western orientalist has made an allegation that the works of Malay scholars are more in the form of translation from famous classical book of fiqh at the time into Malay language. The question is if the allegation is totally true? So the objective of this study is to examine the truth of the allegation by means of al-Sirat al-Mustaqim as text study to refute the allegation.This study is a library research with a focus on data based on the document manuscript al- Sirat al-Mustaqim. The qualitative data is procesed according to specific themes based on historical knowledge and presented in a descriptive manner. The results show the existence of a number of local fiqh issues that were stated by Shaykh Nur al-Din al-Raniri in al-Sirat al-Mustaqim. This proves his sensitivity as a scholar with the Malay community living environment involving Islamic religious law. Hence, this is indirectly dismissed the allegation of the orientalist.